The Roles of The Dance Education Institute and The Ngayogyakarta Hadiningrat Palace in The Inheritance Process of Yogyakarta Classical Dance Style - Saearani, Muhammad Fazli Taib Bin (Harmonia: Journal of Arts Research and Education, 2015)
This study aims to examine the roles of the Ngayogyakarta Palace, formal educational institutions, and non-formal educational institutions in the inheritance of the classical court dance of Yogyakarta or Tari Klasik Gaya Yogyakarta (TKGY). The method employed was a qualitative method through interviews and observations with a number of informants from dance institutions in Yogyakarta. Based on the interviews, a number of independent and collaborative roles among the three types of institutions under study can be identified. These roles were then placed in a theoretical framework related to the inheritance of the classical court dance of Yogyakarta (TKGY) that justifies the reasons why it can be well-inherited in the Special Region of Yogyakarta. Based on this effort, it was found that each institution took a place in the attempt to support the inheritance layers (core, practical, philosophical, and developmental) causing the absence of problems in the existence of the classical court dance of Yogyakarta in the Special Region of Yogyakarta. These findings then can be used as the best practice for the inheritance efforts for classical dances in other places in the Indonesian Archipelago.